Search for the parent material of spring soft wheat resistant to septoria tritici blotch and analysis of the trait inheritance - A. V. Kharina; T. K. Shcheshegova (Аграрная наука Евро-Северо-Востока)
In 2017-2020 in the conditions of Kirov region there were studied 143 varieties, 115 perspective lines and 28 hybrids of the first generation of spring soft wheat according to the degree of resistance to septoria tritici blotch against the background of the natural development of infection. It has been established that development of the disease significantly increased with a decrease in air temperature during the «seedling-tillering» phase (r = -0.83…-0.96) and an increase in the amount of precipitation during «shooting» phase (r = +0.87…+0.90). Resistance to septoria tritici blotch was shown by 16.1 % collection samples. A significant (r = -0.83) decrease in yield by an average of 19 % in susceptible samples compared to resistant ones was revealed. The greatest breeding and immunological value were represented by the varieties of Russian selection: Tobolskaya, Tyumenskaya 29, Moskovskaya 35 and МIS, among which the early variety MIS was tolerant to septoria tritici blotch. Thirteen lines resistant to septoria tritici blotch were identified from the new breeding material. The varieties selected for resistance to septoria tritici blotch were used in hybridization. In F1 hybrids domination and overdomination in the inheritance of resistance to septoria tritici blotch prevailed, as well as weight of 1000 grains and yield per 1 m2. Among them, 8 hybrids F1  with the highest values of the dominance indices were identified. It has been established, that inheritance of resistance to septoria tritici blotch, weight of 1000 grains and yield of hybrids F1 occurs both in the maternal and paternal lines. The greatest immunological effect was obtained when using the varieties Daria (Russia) and Epos (Germany). The most productive hybrids were the variety Daria, taken as both a maternal and paternal form, as well as when using the Egisar 29 (Russia) variety as a maternal form.